Keywords for comics studies - Fawaz, Ramzi; Whaley, Deborah Elizabeth; Streeby, Shelley, 1963- (Keywords series., 2021)
"Across more than fifty essays, Keywords for Comics Studies provides a rich, interdisciplinary vocabulary for comics and sequential art, and identifies new avenues of research into one of the most popular and diverse visual media of the twentieth and twenty-first century. In an original twist on the NYU Keywords mission, the terms in this volume combine attention to the unique aesthetic practices of a distinct medium, comics, with some of the most fundamental concepts of the humanities broadly. Readers will see how scholars, cultural critics, and comics artists from a range of fields-including media and film studies, queer and feminist theory, and critical race and transgender studies among others-take up sequential art as both an object of analysis and a medium for developing new theories about embodiment, identity, literacy, audience reception, genre, cultural politics and more. To do so, Keywords for Comics Studies presents an array of original and inventive analyses of terms central to the study of comics and sequential art, but traditionally siloed in distinct lexicons: these include creative or aesthetic terms like Ink, Creator, Border, and Panel; conceptual terms like trans*, disability, universe, and fantasy; genre terms, like Zine, Pornography, Superhero, and Manga; and canonical terms like X-Men, Archie, Watchmen and Love and Rockets. Written as much for students and lay readers as professors and experts in the field, Keywords for Comics Studies revivifies the fantasy and magic of reading comics in its kaleidoscopic view of the field's most compelling and imaginative ideas"--